COP30 and its climate antecedents: challenges, expectations, and historical lessons for the Conference in Belém (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It traces the trajectory of climate conferences from Stockholm to Dubai, highlighting legal and political advancements. It contextualizes COP-30 as a strategic step that symbolizes the Amazon's leading role and Brazil's leadership in climate cooperation.(Received: September 2025 | Accepted: November 2025)
Keywords: Climate Conferences; International Environmental Law; International Cooperation; Kyoto Protocol; Paris Agreement